Extracellular Recordings of Patterned Human Pluripotent Stem Cell-Derived Cardiomyocytes on Aligned Fibers - Junjun Li; Itsunari Minami; Leqian Yu; Kiyotaka Tsuji; Minako Nakajima; Jing Qiao; Masato Suzuki; Ken Shimono; Norio Nakatsuji; Hitetoshi Kotera; Li Liu; Yong Chen (Stem Cells International)
Human induced pluripotent stem cell (hiPSC) derived cardiomyocytes (CMs) hold high potential for use in drug assessment and myocardial regeneration. To create tissue-like constructs of CMs for extracellular monitoring, we placed aligned fibers (AFs) on the surface of a microelectrode array and then seeded hiPSC-CMs for subsequent monitoring for 14 days. As expected, the CMs organized into anisotropic and matured tissue and the extracellular recordings showed reduced premature beating higher signal amplitude and a higher probability of T-wave detection as compared to the culture without fibers. The CMs on the aligned fibers samples also exhibited anisotropic propagation of the field potential. These results therefore suggest that the hiPSC-CMs cultured on AFs can be used more reliably for cell based assays.